TIPIC syndrome in a patient following sorafenib treatment for acute myeloid leukemia: a rare case report - Chen, Chang; Zhong, Jinman; Hu, Wanzhen; Tan, Jiewen (Frontiers in Oncology, 2024)
Transient Perivascular Inflammation of the\ Carotid Artery (TIPIC) syndrome is uncommon, and cases of TIPIC induced by the targeted drug, sorafenib, are extremely rare. This case report describes a patient with acute myeloid leukemia carrying an FMS‐like tyrosine kinase 3 mutation, who developed TIPIC syndrome, which may have been induced by sorafenib treatment. A 65-year-old woman diagnosed with acute myeloid leukemia experienced severe neck pain and sclerotic blisters on her palms and soles during sorafenib treatment. Carotid ultrasound revealed thickening of the right common carotid artery (RCCA) wall, and magnetic resonance imaging revealed perivascular tissue edema in the distal RCCA. Following clinical and imaging assessments, the patient was diagnosed with TIPIC syndrome. Treatment involved a one-week course of oral steroid therapy with dexamethasone and non-steroidal anti-inflammatory drugs, which led to complete clinical recovery. TIPIC syndrome involves transient nonspecific perivascular inflammation of the carotid adventitia; however, the precise underlying cause remains unclear. In this study, we report a rare case and explore the potential pathophysiological mechanisms through a review of the existing literature.